Using digital image correlation to evaluate fatigue behavior of strengthened reinforced concrete beams. (15th December 2015) - Mahal, Mohammed; Blanksvärd, Thomas; Täljsten, Björn; Sas, Gabriel
Highlights: Beams strengthened with (EBR) plates and near-surface mounted (NSM) bars have been tested under fatigue load. Digital image correlation technique has been used to investigate the performance of strengthened beams. The (DIC) technique can be used to measure the actual mechanical behavior under fatigue load. EBR plate-strengthened beams have lower crack widths and heights than beams strengthened with NSM bars. The greatest change in the curvature range occurs during the first cycle. Abstract: The fatigue behavior of reinforced concrete beams strengthened with externally bonded carbon fiber reinforced polymer (EBR) plates and near-surface mounted (NSM) bars has been investigated using a digital image correlation (DIC) technique. Displacement fields obtained from digital images recorded during specific load cycles in fatigue tests are analyzed to provide information on crack width, beam deflection and curvature, and major principal strains to enable crack detection. The results obtained in this way were compared to data gathered using conventional sensors, revealing that the DIC technique provided very accurate and detailed information, which is not possible to obtain using conventional techniques. The experimental results for plate-strengthened, bar-strengthened and unstrengthened beams are discussed.